Al-4.06Mg-0.74Mn 합금의 해수 내 캐비테이션 환경에 따른 정전위 특성 평가 - 이승준(Seung-Jun Lee); 한민수(Min-Su Han); 장석기(Seok-Ki Jang); 김성종(Seong-Jong Kim) (Biuletyn Uniejowski, 2012)
The hull of a fast sailing aluminium ship are generally prone to erosion owing to the impact of seawater. At this time, synergistic effects of the erosion and the corrosion by aggressive ions such as chlorides tend to aggravate the damage. There have been various attempts, including selection of erosion-resistant materials, cathodic protection and addition of corrosion inhibitors, to overcome damage by erosion or corrosion under marine environments. These approaches, however, have limits on identifying the damage mechanism clearly, because they depend on analogical interpretation by correlating two damage behaviors after the individual studies are assessed. In this research, it was devised a hybrid testing apparatus that integrates electrochemical corrosion test and cavitation test, and thus the erosion-corrosion behavior by cavitation was investigated more reliably. As a result, the slightest damage was observed at the potentials between -1.6 V and -1.5 V. This is considered to be due to a reflection or counterbalancing effect caused by collision of the cavitation cavities and the hydrogen gas formed by activation polarization.